Foreign Body Aspiration of a Dental Bridge in the Left Main Stem Bronchus - Mahmoud, Monay (Hindawi Publishing Corporation, 2012)
Aspiration of tracheobronchial foreign bodies is a life-threatening event that occurs mainly in children. Occurrence in adults is rare and usually has a subtle presentation as most adults are unaware of aspiration of any foreign material. Decreased levels of consciousness, sedation, and neuromuscular diseases are major risk factors for foreign body aspiration in adults. Prompt diagnosis and intervention through foreign body retrieval are critical to prevent significant morbidity and mortality. Retrieval procedure is risky, and sudden decompensation of the patient can occur anytime. We are presenting an adult who accidentally aspirated his dental prosthesis during sleep and underwent successful retrieval of the dental bridge using flexible bronchoscopy.